2011
DOI: 10.1097/ede.0b013e31821c6c58
|View full text |Cite|
|
Sign up to set email alerts
|

Particulate Air Pollution Exposure and C-reactive Protein During Early Pregnancy

Abstract: Background It is not well understood how air pollution leads to adverse pregnancy outcomes. One pathway may be through C-reactive protein, a biomarker of systemic inflammation that has been reported to increase the risk of preterm delivery. We examined whether air pollution influences serum concentrations of C-reactive protein in early pregnancy. Methods We studied 1696 pregnant women in Allegheny County, PA, from 1997 through 2001. C-reactive protein concentrations were assayed in blood collected before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 40 publications
(63 reference statements)
5
96
1
Order By: Relevance
“…Furthermore, inflammation and oxidative stress in the early of pregnancy or toward the end of pregnancy are also related to the onset of parturition. We have previously reported air pollution exposure to be associated with increased C-reactive protein concentrations (>8 μg/ml) in early pregnancy (Lee et al 2011) and a Dutch cohort study recently confirmed these observations (van den Hooven et al 2012a). …”
Section: Introductionmentioning
confidence: 67%
“…Furthermore, inflammation and oxidative stress in the early of pregnancy or toward the end of pregnancy are also related to the onset of parturition. We have previously reported air pollution exposure to be associated with increased C-reactive protein concentrations (>8 μg/ml) in early pregnancy (Lee et al 2011) and a Dutch cohort study recently confirmed these observations (van den Hooven et al 2012a). …”
Section: Introductionmentioning
confidence: 67%
“…Animal studies provide support for this mechanism by demonstrating air pollution exposure can lead to inflammation in the lung (Tamagawa et al 2008) that disrupts insulin action by inducing inflammation in adipose (Sun et al 2009; Xu et al 2011) and vascular tissue (Sun et al 2005; Tamagawa et al 2008). Recently, studies in human populations have also linked air pollution with elevated levels of C-reactive protein (CRP), a marker of systemic inflammation, in healthy young adults (Rich et al 2012), a diabetic population (Khafaie et al 2013) and in pregnant women (van den Hooven et al 2012; Lee et al 2011). CRP levels, in turn, are associated with increased risk of type 2 diabetes (Wang et al 2013) and gestational glucose intolerance (Lowe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…An impaired placental function could be caused by oxidative stress, inflammation, coagulation, impaired endothelial function or haemodynamic responses 3435 Women who were exposed to ambient air particles and ozone during early pregnancy are more likely to have elevated levels of C reactive protein levels, systematic inflammation driven by air pollution exposure being an underlying mechanism behind adverse birth outcomes 35. Trophoblastic invasion during formation of the placenta might be disrupted by proinflammatory cytokines 36…”
Section: Discussionmentioning
confidence: 99%
“…34 35 Women who were exposed to ambient air particles and ozone during early pregnancy are more likely to have elevated levels of C reactive protein levels, systematic inflammation driven by air pollution exposure being an underlying mechanism behind adverse birth outcomes. 35 Trophoblastic invasion during formation of the placenta might be disrupted by proinflammatory cytokines. 36 37 Air pollution in early pregnancy (first trimester) is of particular interest because this is the period when pollutants would be expected to interfere with maternal vascular remodelling processes.…”
Section: Discussionmentioning
confidence: 99%